Enhanced water resistance properties of bacterial cellulose multilayer films by incorporating interlayers of electrospun zein fibers. (December 2016) - Wan, Zhili; Wang, Liying; Yang, Xiaoquan; Guo, Jian; Yin, Shouwei
Abstract: In this work, we developed multilayer bacterial cellulose (BC)-zein films based on the strong BC film as the outer layers and the electrospun zein fibers as the inner layer, to improve the water resistance properties of hydrophilic BC films. The water resistance properties were evaluated by dynamic water absorption measurement and mung beans storage test. The obtained results showed that the incorporation of electrospun zein fibers made the relatively thin and flexible multilayer films become stiffer, while the zein interlayer did not markedly affect the thermal stability and surface properties of films. Compared to pure BC films, the BC-zein films exhibited significantly better water resistance properties, especially under longer zein deposition time (90 and 120 min). This improvement could be mainly due to the inherent hydrophobicity of zein protein. These findings provide the possibility of adopting a multilayer film strategy for the development of BC packaging films with enhanced water resistance properties by incorporating a high barrier interlayer of electrospun zein fibers. Graphical abstract: Highlights: Multilayer BC films with an interlayer of electrospun zein fibers were developed. The incorporation of electrospun zein fibers made the multilayer films become stiffer. Zein interlayer did not markedly affect the surface and thermal stability of films. The multilayer BC-zein films showed significantly better water resistance properties.